2013
DOI: 10.1186/1741-7015-11-6
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis: implications of interleukin-28B polymorphisms in spontaneous and treatment-related clearance for patients with hepatitis C

Abstract: BackgroundSince 2009, several studies have identified single-nucleotide polymorphisms (SNPs) near the gene encoding for interleukin (IL)-28 (IL28B) that are strongly associated with spontaneous and treatment-induced hepatitis C virus (HCV) clearance. Because this large amount of data includes some inconsistencies, we consider assessment of the global estimate for each SNP to be essential.MethodsRelevant studies assessing IL28B polymorphisms associated with sustained virologic response (SVR) and spontaneous cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 106 publications
(98 reference statements)
3
55
0
1
Order By: Relevance
“…Recent studies have demonstrated the effect of some favorable genotypes (the CC and TT genotypes, and the C and T alleles of polymorphisms rs8099917 and rs12979860, respectively) on the response to the standard treatment for chronic hepatitis C, as well as their relationship with spontaneous HCV clearance in mono-and coinfected individuals 29,35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated the effect of some favorable genotypes (the CC and TT genotypes, and the C and T alleles of polymorphisms rs8099917 and rs12979860, respectively) on the response to the standard treatment for chronic hepatitis C, as well as their relationship with spontaneous HCV clearance in mono-and coinfected individuals 29,35 .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the vaccination program has been extended to individuals up to 49 years of age, in addition to all HIV-infected patients 29 . However, as HIV+ individuals respond poorly to the HBV vaccine, regular monitoring of the immunological status in these patients is recommended 30 .…”
Section: Discussionmentioning
confidence: 99%
“…IL28B genotype has been associated with response to pegylated interferon and ribavirin in monoinfected and coinfected populations with a similar effect on outcome in both in a recent meta-analysis [82]. The Sprint 2 study demonstrated response rates to PEG-IFN and RBV with boceprevir were 80%, 71% and 59% with CC, CT and TT genotype respectively [83].…”
Section: Rationalementioning
confidence: 94%
“…Genetic variants of IL28B explain differences in IFN efficacy between races due to different distributions of individual gene alleles [7][8][9][10][11]. Studies on HCV provided an inspiration for investigations of the influence of IL28B polymorphisms on infections with the other hepatotropic viruses, since IFN λ shows broad and non-specific antiviral activity [18].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a single nucleotide polymorphism (SNP) near the IL28B gene was shown to be highly predictive of a sustained viral response (SVR) to PegIFN and ribavirin in chronic C hepatitis. Homozygous genotypes classified as CC at locus rs12979860 were associated with more than twice as high SVR rate in comparison with TT alleles, whereas CT heterozygotes exerted an intermediate treatment response [7][8][9][10]. A favorable CC constellation was also shown to increase spontaneous HCV clearance and predicts better outcomes of HCV reinfection after liver transplantation [11].…”
Section: Introductionmentioning
confidence: 96%